2005
DOI: 10.5194/angeo-23-1259-2005
|View full text |Cite
|
Sign up to set email alerts
|

Low-latitude ionospheric turbulence observed by Aureol-3 satellite

Abstract: Abstract. Using PSD (Power Spectral Density) data on electron density and electric field variations observed on board Aureol-3 satellite at low-to-mid-latitude ionosphere we analyze a scale distribution of the ionospheric turbulence in a form k −α , where k is the wave number and α is the spectral index. At first, high-resolution data in the near-equator region for several orbits have been processed. In this case the frequency range is from 6 Hz to 100 Hz (corresponding spatial scales from 80 m to 1.3 km), eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…These enhancements are symmetrical around the magnetic equator. As was reported in the previous works by Hobara et al (2005b), the observed electric field fluctuations exhibit nearly an identical characteristic as upper ionospheric perturbations and are located on the side of the EA crest. The electric field enhancement near EA is mostly identified during daytime orbits in DEMETER.…”
Section: Data Set and Observationssupporting
confidence: 85%
See 2 more Smart Citations
“…These enhancements are symmetrical around the magnetic equator. As was reported in the previous works by Hobara et al (2005b), the observed electric field fluctuations exhibit nearly an identical characteristic as upper ionospheric perturbations and are located on the side of the EA crest. The electric field enhancement near EA is mostly identified during daytime orbits in DEMETER.…”
Section: Data Set and Observationssupporting
confidence: 85%
“…In this paper we perform the similar data analysis as was reported by Hobara et al (2005b) by using the ELF electric field data from Aureol 3 satellite. They found that mean value of the electric field power during the seismic period is much higher than that for no seismic period.…”
Section: Discussion and Summarymentioning
confidence: 94%
See 1 more Smart Citation
“…The similar kind of ideas was applied to the in-situ data of electron density and electric field observed by different satellites traversing in the upper ionosphere (Cosmos-900 and Aureol-3) Hobara et al, 2005). That is, the fluctuations in the plasma density and electric field in the ionosphere have been investigated in terms of the fractal exponent.…”
Section: Discussionmentioning
confidence: 99%
“…The penetration of AGW waves into the ionosphere leads to modification of the natural (background) ionospheric turbulence Hobara et al, 2005). In this model the ground-based VLF station signals is scattered in the ionospheric turbulence region above the earthquake preparatory zone.…”
Section: Analysis Of Sub-ionospheric Signals Using Demeter Observationsmentioning
confidence: 99%